MADS-Box Transcription Factor MadsA Regulates Dimorphic Transition, Conidiation, and Germination of Talaromyces marneffei - Wang, Qiangyi; Du, Minghao; Wang, Shuai; Liu, Linxia; Xiao, Liming; Wang, Linqi; Li, Tong; Zhuang, Hui; Yang, Ence (Frontiers in Microbiology, 2018)
The opportunistic human pathogen Talaromyces marneffei exhibits a temperature-dependent dimorphic transition, which is closely related with its pathogenicity. This species grows as multinucleate mycelia that produce infectious conidia at 25°C, while undergoes a dimorphic transition to generate uninucleate yeast form cells at 37°C. The mechanisms of phenotype switching are not fully understood. The transcription factor madsA gene is a member of the MADS-box gene family. Previously, it was found that overexpression of madsA gene resulted in mycelial growth instead of yeast form at 37°C. In the current study, the madsA deletion mutant (ΔmadsA) and complemented strain (CMA) were constructed by genetic manipulation. We compared the phenotypes, growth, conidiation, conidial germination and susceptibility to stresses (including osmotic and oxidative) of the ΔmadsA with the wild-type (WT) and CMA strains. The results showed that the ΔmadsA displayed a faster process of the yeast-to-mycelium transition than the WT and CMA. In addition, the deletion of madsA led to a delay in conidia production and conidial germination. The tolerance of ΔmadsA conidia to hydrogen peroxide was better than that of the WT and CMA strains. Then, RNA-seq was performed to identify differences in gene expression between the ΔmadsA mutant and WT strain during the yeast phase, mycelium phase, yeast-to-mycelium transition and mycelium-to-yeast transition, respectively. Gene ontology functional enrichment analyses indicated that some important processes such as transmembrane transport, oxidation-reduction process, protein catabolic process and response to oxidative stress were affected by the madsA deletion. Together, our results suggest that madsA functions as a global regulator involved in the conidiation and germination, especially in the dimorphic transition of T. marneffei. Its roles in the survival, pathogenicity and transmission of T. marneffei require further investigation.